2023
DOI: 10.1186/s42779-023-00208-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring educational traditions and experiences of block residents engaging in urban food self-production: a case study of Urban Living Lab

Ewa Duda,
Adamina Korwin-Szymanowska

Abstract: Food self-production offers a promising solution to many urbanization problems in cities. However, despite the advanced technology, the acceptance and involvement of local residents (its users) are required for implementation. The study presented here aims to gain a deeper understanding of the educational characteristics of future or current users of urban gardens, especially those oriented towards their own food production. The research will explore urban dwellers' traditional understanding and knowledge of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…While there is a growing interest in self-growing food in urban settings, it often lacks in-depth learning. Report from a study conducted by Duda and Korwin-Szymanowska [46] revealed that food is grown as a necessity or routine and that passing on knowledge was not a priority. Deikmann [47] suggested that the educational experiences within gardens can act as a precursor to heightened food advocacy and democratic engagement with the food system, contributing to social cohesion.…”
Section: Educational Opportunitiesmentioning
confidence: 99%
“…While there is a growing interest in self-growing food in urban settings, it often lacks in-depth learning. Report from a study conducted by Duda and Korwin-Szymanowska [46] revealed that food is grown as a necessity or routine and that passing on knowledge was not a priority. Deikmann [47] suggested that the educational experiences within gardens can act as a precursor to heightened food advocacy and democratic engagement with the food system, contributing to social cohesion.…”
Section: Educational Opportunitiesmentioning
confidence: 99%